Customer Engagement on Purchase: The Role of Sharing Intention in Influencing Consumer Interest in Snack Food Products - Yacob, Syahmardi; Dewi , Erwita; Siregar , Ade Perdana (MSJ : Majority Science Journal, 2025)
Opportunities for MSMEs are indeed wide open with technological advances, but competition in business is increasingly competitive. One can observe that the food sector in Jambi Province is the highest business sector on the MSME scale, so this shows that competition will also be higher. Customer involvement  is considered to foster the intention of new consumers to make purchases, so customer engagement is an important thing to measure in the marketing concept. Food products are not only a business but also a consumer experience in shopping to consume or interact which can potentially increase sales through creating good consumer purchasing intentions. Measuring the intention to share in social commerce needs to be differentiated based on the purpose, namely social or commercial, so that we can further explore the factors of intention to create purchase intention in other consumers. The purpose of this research is to (1) To examine how much influence consumer engagement has on social sharing intentions and commercial sharing intentions directly on Snack Food MSMEs in Jambi Province on; (2) Examining how much influence social sharing intentions and commercial sharing intentions have on purchasing intentions among Snack Food MSMEs in Jambi Province; (3) Examining how much purchasing intentions are influenced by consumer engagement through social sharing intentions and commercial sharing intentions in Snack Food MSMEs in Jambi Province. This study employs Structural Equation Modeling (SEM) for data analysis, utilizing the SmartPLS software